Clinical Observation of General Anesthesia Combined with Spinal Anesthesia in Elderly Patients with Chronic Obstructive Pulmonary Disease. (21st August 2022) - Chen, Jie; Wang, Jing; Duan, Xiaohui; Ping, Fumin; Zhang, Aiming
Abstract : Objective . This work is aimed at evaluating the efficacy and safety of general anesthesia (GA) combined with spinal anesthesia (SA) (GA+SA) in elderly patients with chronic obstructive pulmonary disease (COPD). Methods and Material . 50 elderly COPD patients were rolled randomly into a control group (simple GA) and observation group (GA+SA). The differences in operation time, postoperative recovery time (PRT), language expression time (LET), anesthetic dosage (AD), catheter extubation time (CET), respiratory circulation indicators (mean arterial pressure (MAP), heart rate (HR), SaO2, and PaO2 ), postoperative VRS score, pulmonary function (forced vital capacity (FVC)), forced expiratory volume in 1 s (FEV1)/FVC and forced expiratory flow (FEF 25% 75%), serum inflammatory factors (IL-6, IL-8, and TNF- α ), Short Portable Mental Status Questionnaire (SPMSQ) score, and the incidence of respiratory system events were analyzed. Results . The results showed that the PRT, LET, AD, and CET of the observation group were all shorter (P < 0.05 ). The postoperative MAP, HR, SaO2, and PaO2 levels of patients who received GA+SA were much higher than those who received simple GA (P < 0.05 ). The postoperative VRS score of the observation group was better than that of the controls (P < 0.05 ). The postoperative pulmonary function of patients in the observation group was better compared with that in the control group (P < 0.05 ). The postoperative serum inflammatory factors in the observation group were lower in contrast to the patients who received simple GA (P < 0.05 ). The postoperative cognitive function SPMSQ score of patients who received GA+SA was lower compared with the score of patients who received simple GA (P < 0.05 ). However, the probability of respiratory system events in the observation group was lower (P < 0.05 ). Conclusion . In conclusion, GA+SA could significantly shorten the PRT and improve the recovery quality of elderly COPD patients. It can also reduce the postoperative inflammatory response and strengthen the pulmonary function and cognitive function. It also enhances the analgesic which is beneficial to patients' postoperative recovery. Therefore, GA+SA was a highly effective and safe anesthesia method for elderly patients with COPD, and it was worthy of clinical application.